Sekuritisasi Pacific Solution: Studi Kasus Implementasi Kebijakan Penahanan Luar Negeri Australia di Nauru - Febby Febby; Rohma Rohma; Nurul Nikita Nasution; Hani Libria Gaisyah (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2025)
Australia has restored offshore detention to Nauru through the Pacific Solution despite continuing criticism globally and violations of human rights. Its continuation raises the question of how this highly debatable policy can still exist. Securitization theory is used in this study to show how asylum seekers are considered threats, resulting in strong state measures to maintain their safety. The study seeks to investigate how the Australian government and media support offshore detention, and to examine the tactics used by humanitarian organizations to challenge this approach. A qualitative case study approach is used in the study, which involves critical discourse analysis to look at political statements, media reports, and advocacy materials from 2024. An examination of the situation shows that both political figures and media used alarming and negative language to describe asylum seekers. These narratives changed public opinion and helped people think offshore detention was necessary for security. Critically, discussions advocating legal and moral points of view remained largely confined to a small audience. The conclusion is that this policy works only by being discussed as a security threat rather than its effects on the crisis.